Perancangan Interior Pusat Ekspresi dan Apresiasi Komunitas Indie di Surabaya - Akzel Gamos A.P (Intra, 2013)
Expression and Appreciation interior design center for Indie Community in Surabaya "or called Indie Art Center is a place for the artists to express themselves and work as well as to gain an appreciation of the general public to provide direct observation and appreciation of works of art proficiency level. Indie art center based in East Java, which is located in the city of Surabaya is expected to accommodate a variety of work and creativity of the indie community can accommodate diversity event showcases. Indie Art Center's design with the theme sounds of change refers to the fighting spirit of the indie community to speak out loud and express their feelings, opinions and aspirations that contain the propaganda messages that are not directly bring changing to the world for the better world.